Development and Evaluation of Natural Gum-Based Sustained-Release Tablets for Levosulpiride and Alprazolam - Dwivedi, Manu; Sharma, Neeraj; Lall, Deepesh; Chaudhari, Shivam; Choudhary, Ram; Singh Rathore, Udaybhan (Journal of Neonatal Surgery, 2025)
Natural gums derived from plants, being both renewable and biocompatible, offer promising uses in pharmaceutical formulations. In this research, hydrophilic gums obtained from Velama, Rekka, and Mardi plants were analyzed for their potential in sustained-release tablet formulations. The gums extracted displayed adequate yields and beneficial physicochemical characteristics, such as low moisture content and approximately neutral pH, suggesting their appropriateness for moisture-sensitive medications and minimized irritation. Micromeritic assessments validated acceptable flow characteristics, while FTIR spectra revealed the existence of functional groups favorable for matrix creation. Sustained-release tablets containing Levosulpiride and Alprazolam were developed using a mixture of these natural gums. Both preformulation and post-compression assessments indicated outstanding compatibility, mechanical strength, and stability under accelerated conditions. In vitro and in vivo investigations demonstrated controlled drug release profiles, with Velama and Mardi gums exhibiting better matrix-forming abilities compared to Rekka gum. This research underscores the effectiveness of natural polymers in improving drug release efficiency, dosing precision and patient adherence in pharmaceutical applications..